The association between living conditions and health among Syrian refugee children in informal tented settlements in Lebanon. (24th October 2019) - Habib, Rima R; Ziadee, Micheline; Abi Younes, Elio; El Asmar, Khalil; Jawad, Mohammed
Abstract: Background: This cross-sectional study explores the relationship between housing, social wellbeing, access to services and health among a population of Syrian refugee children in Lebanon. Methods: We surveyed 1902 Syrian refugee households living in informal tented settlements in Lebanon in 2017. Logistic regressions assessed relationships between housing problems, socioeconomic deprivation, social environment and health. Results: Of the 8284 children in the study, 33.0% had at least one health problem. A considerable number of households (43.1%) had > 8 housing problems. Children in these households had higher odds to have three or more health problems compared to children in households with < 6 housing problems (adjusted odds ratio [AOR], 2.39; confidence interval [CI], 1.50–3.81). Nearly three-quarters (74.3%) of households were severely food insecure. Children in these households had higher odds to have one health problem than those in food secure households (AOR, 1.75; CI, 1.11–2.76). There was a significant positive association between households that reported being unhappy with their neighbourhood and the number of children with health problems in those households. Conclusions: This study highlights the association between the physical and social living conditions and refugee children's health. Without multidimensional interventions that consider improvements to living conditions, the health of young Syrian refugees will continue to worsen.